First-principles study on the adsorption of NO2 gas on Al-doped ZnO (001) and (100) surfaces. Issue 1 (10th September 2022) - Liu, Jin; Li, Yadong; Long, Yan; Lan, Chao; Lv, Yuanyuan; Zhang, Zhiyong; Zhang, Weihu; Wang, Anyi; Tian, Feng
Abstract: The structure model of Al-doped ZnO (001) and (100) surface adsorbing NO2 is constructed. Based on the first-principles method of density functional theory, the energy band, adsorption energy and density of state are calculated using the Castep software package. The Al doping significantly increases the energy and adsorption energy of ZnO(001) and ZnO(100) crystal plane systems, and promotes the transfer of charge from NO2 to ZnO(001) and ZnO(100) surface, which promotes the Fermi energy level to move to the high energy potential, resulting in the decrease of the band gap width, thereby enhancing the adsorption capacity of NO2 gas molecules.